Gestión logística y productividad laboral en Electro Oriente ciudad de Caballococha 2024 - Vargas Badureles, Paul Efrain (2025)
The study seeks to establish a relationship between logistics management and labor productivity in the Electro Oriente company of Caballococha during 2024. The methodology adopted is quantitative, with a focus on obtaining precise numerical data. A descriptive and non-experimental design will be used to observe and describe the variables without manipulation, in addition to a correlational design to explain the relationship between these variables. The most significant results reveal a Spearman correlation coefficient of 0.781** with a p-value of 0.000**. The conclusions highlight the correlation between the variables scrutinized. This validates the hypothesis raised and underlines the importance of effective logistics management to improve labor productivity in the evaluated context.